Digital transformation as an enabler of sustainability innovation and performance – information processing and innovation ambidexterity perspectives - Lu, Hui Ting (2023)
As sustainability gains increased importance among investors and regulators, firms are resorting to digitalization as a means to facilitate innovations and significantly improve their sustainability performances. Drawing on innovation ambidexterity and information processing theory, a framework was curated to assess the effect of digital transformation factors on sustainability innovation ambidexterity as well as sustainability performance. A survey questionnaire was administered to 187 maritime professionals who held relevant roles in innovation, performance management, sustainability, or digitalization. The data collected was then assessed using structural equation modelling, which revealed that the factors influencing sustainability performance, in decreasing order of importance, were digital capabilities, digital technology and business strategy alignment, sustainability exploration innovation, sustainability exploitation innovation, and digital flexibility. These findings contribute to the existing literature by employing the concepts of the identified theories to examine the triadic relationship between digital transformation factors, sustainability innovation ambidexterity, and sustainability performance. This provides a deeper understanding of the interactions between variables that lead to sustainability performance. In addition, it offers directions for managers to enhance sustainability performance through resource optimization in prioritizing training for employees, portfolio management, scheduling regular meetings between information technology and business management teams, and adopting forward-looking approaches to implement digital architecture.